The Effect Of Working Capital Management And Fixed Assets Investment On Profitability (Study On Automotive And Component Companies Listed On The Indonesian Stock Exchange) - Bustanul Arifin; Adnan Farli Fadillah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Politeknik Piksi Input Serang, 2023)
Purpose - This study aims to analyze the influence of working capital management and investment in fixed assets towards profitability. Design/methodology/approach - This research was implemented in the automotive and part companies listed on the Indonesia Stock Exchange for the period 2006 – 2014. The sample was taken using the method of purposive sampling. Eight companies were selected for a sample. Used multiple regression analysis as statistical method Finding - The results of the research show that CCC and AP have negative and considerable influence on ROA, AR have positive and not considerable influence on ROA, while IVR and FAT have positive and considerable influence on ROA. LVR as a control variable has a negative and not significant effect on ROA, while NPM has a positive and considerable influence on ROA Originality - Keyword - working capital management, investment in fixed assets, profitability, return on assets, cash conversion cycle, average collection period, average payment period, inventory conversion period, leverage, net profit margin. Paper Type – Research Paper